Application of microscopy technology in mathematical modeling of hollow fiber membrane system - Lock, S.S.M. (American Institute of Physics Inc., 2015)
Mathematical modeling becomes an indispensable tool in the design process of membrane system by predicting the required module specification and membrane characteristic that are optimum according to various operating conditions. However, challenges are often encountered in determining the effective separation area for mathematical modeling of the hollow fiber membrane system, which are associated with many fine hollow fibers. In this work, the microscopy technology has been adapted to determine the specification of the hollow fiber and packing fraction of the membrane system, before being applied alongside numerical solution to describe the separation performance of a countercurrent hollow fiber membrane system. The accuracy of the methodology has been validated through experimental work. The promising result enables further application of the methodology in industrial scale hollow fiber membrane module design with approximately ten to hundreds of thousands of extremely fine hollow fibers. Â© 2015 AIP Publishing LLC.